The protective effects of S14G-humanin (HNG) against streptozotocin (STZ)-induced cardiac dysfunction. Issue 1 (1st January 2021) - Chen, Xiaopan; Yun, Chuan; Zheng, Hailong; Chen, Xu; Han, Qianfei; Pan, Hua; Wang, Yang; Zhong, Jianghua
ABSTRACT: Excessive oxidative stress, inflammation, and myocardial hypertrophy have been associated with diabetic cardiomyopathy (DCM). S14G-humanin (HNG) is a potent humanin analogue that has demonstrated cytoprotective effects in a variety of cells and tissues. However, the pharmacological function of HNG in diabetic cardiomyopathy has not yet been reported. In the present study, we investigated the protective effects of HNG against streptozotocin (STZ)-induced cardiac dysfunction in diabetic mice. Myocardial hypertrophy in diabetic mice was determined using Wheat Gem Agglutinin (WGA) staining. The heart function was measured with Echocardiographic imaging. Levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) proteins in plasma were measured using enzyme-linked immunosorbent assay (ELISA) kits. Protein expression of Phosphorylated p38/p38 was determined using western blots. We found that HNG treatment attenuated the STZ-induced myocardial hypertrophy and significantly improved heart function. Also, its treatment proved effective as it reduced the levels of several myocardial injury indicators, including creatine kinase-MB (CK-MB), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and both the cardiac and plasma levels of TNF-α and IL-6, highlighting its effect on the STZ-induced myocardial injury. Lastly, HNG suppressed the activation of the p38/nuclear factor kappa-B (NF-κB) signaling pathway. S14G humanin possesses protective effects against streptozotocin-induced cardiac dysfunction through inhibiting the activation of the p38/NF-κB signaling pathway.